Trait and state anxiety is marked by increased working memory-related parietal BOLD signal. (30th August 2018) - Ford, Talitha C.; Simpson, Tamara; McPhee, Grace; Stough, Con; Downey, Luke A.
Highlights: Neural markers of anxiety can be elucidated in non-clinical groups. 2-back performance was comparable between high and low trait anxiety. Anxiety associated with increased bilateral posterior parietal BOLD signal. Anxiety not associated with prefrontal BOLD signal. Non-clinical anxiety affects the recruitment of posterior parietal resources. Abstract: Anxiety is associated with compromised cognitive control functions, such as working memory. State and trait anxiety within the non-clinical population can be utilised to investigate potential neural markers for anxiety, which may help to elucidate potential prevention and intervention methods. Thirty-two healthy adults (20 female, 12 male), aged between 30 and 65 years, performed a 2-back task whilst fMRI BOLD signal was acquired using a 3T scanner. Mean BOLD signal was obtained in cognitive control network regions of interest of: left and right dorsolateral prefrontal cortex (DLPFC) and posterior parietal lobe (PPL), and medial prefrontal cortex (MPFC). State and trait anxiety levels were recorded. Higher overall anxiety was moderately associated with more left and right PPL BOLD signal; there was a weak relationship between anxiety and left DLPFC BOLD signal. MPFC BOLD signal and trait anxiety were moderately associated with overall 2-back task performance. These findings suggest that non-clinical anxiety affects the recruitment of cortical resources during working memory, but that anxiety does not impair performance during a 2-back task.